MENGEMBANGKAN SOFT SKILL SISWA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DI SMKN 3 PALANGKA RAYA - Agustina, Meylinda; Muslimah, Muslimah; Gofur, Abdul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research was conducted with the intention of developing students' soft skills through the implementation of the Problem Based Learning (PBL) learning model in Islamic Religious Education subjects at SMKN 3 Palangka Raya. Non-technical skills such as critical thinking skills in solving problems, effective interpersonal communication, and collaboration in groups, are important aspects that students must have in order to face challenges in the professional world. The research approach used was Classroom Action Research (CAR), by adopting the spiral model from Kemmis and McTaggart which includes the stages of planning, action, observation, and reflection. A total of 30 students from class X Culinary 2 were used as subjects in this study, but only 28 students were consistently involved in each learning cycle. The analysis technique used was descriptive quantitative, with data collection methods in the form of observation, questionnaire distribution, documentation, and in-depth interviews. The findings showed that the percentage of soft skill mastery increased, from 76.48% in the first cycle to 78.00% in the second cycle, both of which were included in the